The Requirements of Immovable Asset Information: A Conceptual Framework for Geoinformation Technology - Salfarina Samsudin, Robiah Suratman, Maimunah Sapri, Norshafadila Ngadiman, Zulkepli Majid, Azman Ariffin, Nor Suhaibah Azri, 8Norhadija Darwin (International Journal of Advanced Science and Technology, 2020)
Geoinformation technology provides significant information for building owners and managers for them to look after the assets and facilities using the same data and software. This is important for decision-making and performance improvement purposes. In Malaysia, theImmovable Asset Management Procedures (TPATA) provided by the federal government is used to guide all government agencies in managing various assets or property owned by the government. While the TPATA focuses on the procedures of utilisation and disposal of immovable assets, this study defines the potential of geoinformation technology to embed with the TPATA system. Thus, this study explains the details of assets information requirements for developing software in improving the current system. Johor Bahru City Council (MBJB) was the case study in which the halls owned by MBJBwere selected for data collection. The findings of this studyprovide the information base which is also known as the core data model.It describes the main elements of physical assets and facilitiesi.e.i) information of premise, ii) land data of premise, iii) internal building blocks of on-premises data (specific asset and its components), iv) external building blocks and other facilities of on-premises data (specific asset and its components), and v) system of premise and management or service of assets data. Finally, the conceptual framework innovated by the TPATA was developed to improve the existing system that provides better accessible touser data. This helps the government to compile, facilitate and maximize its immovable asset data management for a greater accessible system.